Uzon volcano caldera (Kamchatka): A unique natural laboratory of the present-day naphthide genesis - Kontorovich A.E.; Bortnikova S.B.; Karpov G.A.; Kashirtsev V.A.; Kostyreva E.A.; Fomin A.N. (My University, 2011)
Oil shows from the thermal springs of the Uzon volcano caldera have been studied by gas chromatography–mass spectrometry methods. Based on the composition and distribution of biomarker molecules, their genetic identity with the organic matter of Pliocene–Quaternary deposits has been established. It has been shown that the Uzon caldera is a unique natural laboratory of the present-day oil formation from the organic matter of Pliocene–Quaternary sediments. It has been stated that attempts to consider the compounds forming these oil shows as a product of hydrothermal abiogenic synthesis are absolutely unfounded.
Keywords: 38.61.19 Минеральные, термальные воды и рассолы; Узон; Kamchatka; Кайнозой::Неоген::Плиоцен; Кайнозой::Четвертичная